2020
DOI: 10.3390/fluids5040195
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Performance of a Heated Pipe in the Presence of a Metal Foam and Twisted Tape Inserts

Abstract: To meet the demand for more efficient ways of cooling and heating, new designs and further development of heat exchangers is essential in industry. The present study focuses on the thermal performance of a circular pipe with two inserts. The first insert consists of a porous medium having a porosity of 0.91, and the second one consists of a single twist solid insert. Different ranges of heating conditions have been applied for different flow rates. Water and titanium dioxide (TiO2) nanofluid 1% vol are the liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The optimal concentration was selected by calculating the thermal efficiency ratios for each concentration, and on that basis, SiC-water with a 3%wt concentration was deemed to be the optimal concentration. Saghir et al [34] investigated the effects of a porous copper insert and a copper twisted tape insert in a pipe where water and TiO2-water were the working fluids of the system. A heat flux of 50000W/m 2 was applied to the mid section of the pipe.…”
Section: Inlet Temperature Of Water (K) 308mentioning
confidence: 99%
“…The optimal concentration was selected by calculating the thermal efficiency ratios for each concentration, and on that basis, SiC-water with a 3%wt concentration was deemed to be the optimal concentration. Saghir et al [34] investigated the effects of a porous copper insert and a copper twisted tape insert in a pipe where water and TiO2-water were the working fluids of the system. A heat flux of 50000W/m 2 was applied to the mid section of the pipe.…”
Section: Inlet Temperature Of Water (K) 308mentioning
confidence: 99%
“…A channel (or duct) with a backward facing step (BFS) can be regarded as an archetypal system for the analysis of many problems with practical or technological relevance. Inherently multidisciplinary, this fundamental fluid-dynamic subject really stands at the interface between different technological fields, which include (but are not limited to) mechanical, civil and aeronautical engineering (e.g., the interaction of gas currents with vehicles, buildings and airfoils at a large angle of attack, see, e.g., Skinner and Behtash [1] , Omidvar et al [2] ), thermal engineering (combustors, condensers, industrial heat exchangers, see, e.g., Delgado-Buscalioni and Crespo del Arco [3] ; Plant and Saghir [4] ; Papazian et al [5] ; Brottier and Bennacer [6] ; Souissi et al [7] ), and many other strictly related applications (e.g., the cooling of nuclear reactors, power plants and various types of electronic equipment, Sun and Jaluria [8] ).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that all twisted tapes with non-uniform length had higher heat transfer coefficient and Nusselt number values than uniform twisted tape length. An article by K. Papazian et al [22] looks at thermal performance and efficiency of a circular pipe with two inserts, one with a porous medium with porosity of 0.91, and the other a single twist solid insert. It was determined that the twisted tape insert increases thermal efficiency than the porous media insert.…”
Section: Introductionmentioning
confidence: 99%